Newcomer Psychologists and Organizational Socialization: Can a Content Model Capture the Experience? - Ingvild Sagberg (Scandinavian Journal of Work and Organizational Psychology, 2016)
The purpose of this article is to evaluate how well Taormina’s Multidomain, Continuous Process Model of Organizational Socialization (Taormina, 1997) applies to the data from qualitative interviews with newcomer psychologists, and to explore the interview content that does not correspond with the model. A total of 64 interviews with 22 recently graduated psychologists in Norway were subjected to deductive content analysis by use of the model. The interview content that did not fit with the model was then explored by inductive content analysis. Largely, the model covered the interview material. However, the model’s categories are wide, and perhaps they too easily embraced the data. Moreover, the model did not embrace issues concerning the work/non-work interface and the participants’ own health and well-being, and an extension of the model is therefore discussed. These issues may be relevant in other professional contexts as well, and not only to newly graduated employees. The findings suggest that organizational socialization researchers could benefit from expanding their view of newcomers’ situation. To practitioners in the field of HR, the model may provide a framework for developing introductory programmes. In addition, attention to the newcomers’ personal well-being and life situation in general is recommended.